Design of a low cost concrete rooftile making machine - Mahmod, Hamzah (2010)
This thesis is written based on the steps and processes done on the designing of a low cost Concrete Roftile Making Machine. It follows according to Design and Development Standard and Boothroyd Dewhurst Design for Manufacturing and Assembly (DFMA) Methodology. The machine functions like a stamping machine, which presses concrete slurry between upper and lower mold. Concrete slurry manually loaded onto lower mold and pressed by upper mold by using hydraulic pressure to form concrete rooftile. After that the pressed concrete rooftile together with the lower mold assembly is pulling out to move wet rooftile for drying and secondary process. This machine satisfy the demand for the small and medium size industries because of its design, functionality and price. The measurements of the performance also being analyzed by considering the design of structure, design of hydraulic and electrical, stress analysis and safety for each component of the machine and finally come out with product (machine) design specification.